Gunter Grass – pisarz prowokujący - Tomczak, Maria (Studia Europaea Gnesnensia, 2012)
The article presents the political profile of the German writer and Nobel prize winner, Günter Grass, and the singular nature of his involvement in German political life. Grass’s views, albeit internally inconsistent, had been comprehensible until the Unification of Germany, while his political activity strove do defend such values as liberty, democracy and moderation. After the unification, of which he had been an adversary, Grass began to speak in ever more controversial tones, and his views seem to clash more and more profoundly with what he had formerly advocated.